Endothelin-1 Upregulates Activin Receptor-Like Kinase-1 Expression via Gi/RhoA/Sp-1/Rho Kinase Pathways in Human Pulmonary Arterial Endothelial Cells - Sugimoto, Koichi; Yokokawa, Tetsuro; Misaka, Tomofumi; Kaneshiro, Takashi; Yamada, Shinya; Yoshihisa, Akiomi; Nakazato, Kazuhiko; Takeishi, Yasuchika (Frontiers in Cardiovascular Medicine, 2021)
Background: Pulmonary arterial hypertension (PAH) is characterized by pulmonary vasoconstriction and organic stenosis. It has been demonstrated that endothelin-1 (ET-1) induces pulmonary vasoconstriction through activation of RhoA. In addition, a gene mutation of activin receptor-like kinase (ACVRL)-1 is recognized in PAH patients. However, little is known about the association between ET-1 and ACVRL-1. Objective: In the present study, we investigated the effect of ET-1 on ACVRL-1 expression and aimed to delineate the involvement of the Gi/RhoA/Rho kinase pathway. Methods: ET-1 was added to culture medium of human pulmonary arterial endothelial cells (PAECs). Pretreatment with pertussis toxin (PTX) or exoenzyme C3 transferase (C3T) was performed for the inhibition of Gi or RhoA, respectively. Rho kinase was inhibited by Y27632. Mithramycin A was used for inhibition of Sp-1, which is one of the transcriptional factors of ACVRL-1. Active form of RhoA (GTP-RhoA) was assessed by pull-down assay. Results: ACVRL-1 expression was increased by ET-1 in the PAECs. Pull-down assay revealed that ET-1 induced a GTP-loading of RhoA which was suppressed by pretreatment with PTX or C3T. Further, PTX, C3T, and Y27632 suppressed the ET-1-induced ACVRL-1 expression. ET-1 increased the activity of ACVRL-1 promotor and stabilized the ACVRL-1 mRNA. Sp-1 peaked 15 min after adding ET-1 to the PAECs. PTX and C3T prevented the increase of Sp-1 induced by ET-1. Inhibition of Sp-1 by mithramycin A suppressed the ET-1 induced ACVRL-1 upregulation. Conclusion: The present study demonstrated that ET-1 increases ACVRL-1 expression in human PAECs via the Gi/RhoA/Rho kinase pathway with involvement of Sp-1.